Access Contested : Security, Identity, and Resistance in Asian Cyberspace - Deibert, Ronald (Book collections on Project MUSE., 2012)
This volume examines the interplay of national security, social and ethnic identity, and resistance in Asian cyberspace offering in-depth accounts of national struggles against Internet controls as well as updated country reports by ONI researchers.